Phospholipase C inhibits apoptosis of porcine oocytes cultured in vitro. Issue 7 (3rd January 2020) - Chen, Hua Li; Cheng, Jian Yong; Yang, You Fu; Li, Yuan; Jiang, Xiao Han; Yang, Li; Wu, Lin; Shi, Meihong; Liu, Boyang; Duan, Jiaxin; Li, Xiaoya; Li, Qing Wang
Abstract: Oocyte apoptosis can be used as an indicator of oocyte quality and development competency. Phospholipase C (PLC) is a critical enzyme that participates in phosphoinositide metabolic regulation and performs many functions, including the regulation of reproduction. In this study, we aimed to explore whether PLC participates in the regulation of apoptosis in porcine oocytes and investigated its possible mechanism. In porcine oocytes, 0.5 μM U73122 (the PLC inhibitor) was considered to be the best concentration to facilitate maturation, and 0.5 μM m‐3M3FBS (the PLC activator) was regarded as the most appropriate concentration to inhibit maturation. The percentage of cleavage and blastocysts treated with 0.5 μM U73122 was lower than that of the control group. Furthermore, the percentage of cleavage and blastocysts treated with 0.5 μM m‐3M3FBS was higher than that of the control group. The relative PLC messenger RNA (mRNA) expression tested by a quantitative real‐time polymerase chain reaction was found to be inhibited by 0.5 μM U73122 or activated by 0.5 μM m‐3M3FBS. The relative mRNA abundance of BAK, BAX, CASP3, CASP8, and TP53 and protein abundance of Bak, cleaved caspase‐3, caspase‐8, and P53 was activated by U73122 or inhibited by m‐3M3FBS, while the relative mRNA and protein level of BCL6 showed the opposite trend. The intracellular Ca 2+ concentration increased and the expression of PLCB1 protein also increased in porcine oocytes when they were cultured with 0.5 μM m‐3M3FBS for 44 hours. The abundance of proteins PKCβ and CAMKIIα and the expression of several downstream genes ( CDC42, NFATc1, NFATc2, NFκB, and NLK ) were activated by m‐3M3FBS or inhibited by U73122. Our findings indicate that PLC inhibits apoptosis and maturation in porcine oocytes. The intracellular Ca 2+ concentration, two Ca 2+ ‐sensitive proteins, and several downstream genes were positively regulated by PLC. Abstract : The present study indicates that phospholipase C could play a role in inhibiting apoptosis and maturation and increasing the rate of cleavage and blastocysts in porcine oocytes. The intracellular Ca 2+ concentration, two Ca 2+ sensitive proteins, and several downstream genes were positively regulated by PLCB1.